2022
DOI: 10.1021/acs.macromol.2c00489
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Block-Random Copolymer Stabilizers: A “Seeded-Coagulative” Emulsion Polymerization Mechanism

Abstract: Polystyrene-b-[polystyrene-r-poly(acrylic acid)] block-random copolymers are effective stabilizers of emulsion polymerizations but exhibit unusual dispersion behavior, selfassembling with low aggregation numbers or possibly self-folding into single-chain nanoparticles. In emulsion polymerizations stabilized by these block-random copolymers, the total final particle surface area was directly proportional to the stabilizer concentration and was unaffected by kinetically driven processes such as initiation and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…As the feeding proceeds, the pH of the emulsion decreases to 6.5 because of the decomposition of APS initiator. 38 While the reference experiment ( pH i = 9.5) displays the previously reported trend for BRCs with increasing particle diameter (and a decrease of N p ) with increasing conversion because of the coagulation of the growing particles, 26 the pH = 7.9 experiment displays a different behaviour. The D n was found to decrease abruptly in the early stages and remain relatively constant until the end of polymerisation.…”
Section: Papermentioning
confidence: 53%
See 1 more Smart Citation
“…As the feeding proceeds, the pH of the emulsion decreases to 6.5 because of the decomposition of APS initiator. 38 While the reference experiment ( pH i = 9.5) displays the previously reported trend for BRCs with increasing particle diameter (and a decrease of N p ) with increasing conversion because of the coagulation of the growing particles, 26 the pH = 7.9 experiment displays a different behaviour. The D n was found to decrease abruptly in the early stages and remain relatively constant until the end of polymerisation.…”
Section: Papermentioning
confidence: 53%
“…A unique, seeded-coagulative nucleation mechanism was proposed where a large population of small BRC aggregates act as seeds which coagulate as the polymer particles grow. 26 This seeded-coagulative mechanism showed no change in total stable particle surface area at a given concentration of BRC when kinetic factors ( e.g. initiation rate) were modified, suggesting a robust mechanism.…”
Section: Introductionmentioning
confidence: 86%
“…Detailed information on the evaluation of copolymer aggregates as well as the emulsion properties of the final latex is presented in a previous study. [16] 3 | RESULTS AND DISCUSSION…”
Section: Procedures For Emulsion Polymerizationmentioning
confidence: 99%
“…It was shown that PS- b -(PS- r -PAA) could successfully stabilize styrene emulsion polymerizations when at least a 3 wt % stabilizer relative to a monomer was used. In addition to the unique nucleation mechanism observed in emulsion polymerization, these copolymers presented an unanticipated ease of dispersion, especially given what has been observed for analogous block copolymers . It was proposed that the facile process leading to transparent dispersions at concentrations upwards of 300 g/L is in part due to self-folding into single-chain nanoparticles as opposed to the self-assembly behavior commonly observed with block copolymers and small-molecule amphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously reported the use of PS- b -(PS- r -PAA) “block-random” copolymers (BRCs) as stabilizers in emulsion polymerization. , These materials are highly hydrophobic, with less than 30 mol % acrylic acid overall, unlike previous reports of PS-PAA gradient copolymers, where it was assumed that more acrylic acid than styrene was required to enable dispersion of copolymers. It was shown that PS- b -(PS- r -PAA) could successfully stabilize styrene emulsion polymerizations when at least a 3 wt % stabilizer relative to a monomer was used.…”
Section: Introductionmentioning
confidence: 99%